Role of complement in the pathogenesis of experimental autoimmune myasthenia gravis (The Rockefeller University Press, 1978)
An acute phase of experimental autoimmune myasthenia gravis (EAMG) occurs transiently early in the immune response of Lewis rats to nicotinic acetylcholine receptors (AChR) when Bordetella pertussis is used as adjuvant. It is characterized by a destructive cellular attack directed at the postsynaptic membranes of muscle. Acute EAMG can be passively transferred to normal rats by IgG from serum of rats with chronic EAMG. In the present study, acute EAMG, induced either by passive transfer of syngeneic antibodies or by active immmunization, was inhibited in rats depleted of complement by treatment with cobra venom factor (CoF). Furthermore, passive transfer of antibodies in excess of the muscle's content of AChR was without any measurable effect in rats treated with CoF. Although 60% of the muscle's AChR was complexed with antibody, there was no reduction in the muscle's content of AChR, and neuromuscular transmission was not compromised as judged electromyographically by curare sensitivity. These data imply that redistribution, accelerated degradation, and impairment of the ionophore function of AChR, effects of antibodies described in vitro on extrajunctional AChR, do not play a significant role in vivo in impairing neuromuscular transmission in an intact neuromuscular junction. Complement appears to be a critical mediator of anti-AChR antibodies' pathogenicity in vivo.